PEMBELAJARAN KAYANG MELALUI PENDEKATAN BERMAIN â€œRAMBOâ€ PADA SISWA KELAS IV SEKOLAH DASAR NEGERI KAJAR KECAMATAN LASEM KABUPATEN REMBANG TAHUN PELAJARAN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
ThisÂ classroomÂ actionÂ researchÂ consisted of twoÂ cycles,Â eachÂ cycleÂ includes:Â planning,Â action,Â observationÂ andreflection.Â Prior to the study, the learning outcomes KayangÂ Elementary School fourthÂ gradeÂ students Kajar asmanyÂ as 18 of t he 24Â children (66%)Â did notÂ pass KKM with anÂ averageÂ value of 6.54.Â Based on the results ofthisÂ studyÂ illustratedÂ thatÂ Â theÂ implementationÂ ofÂ learningÂ throughÂ playÂ kayangÂ wallÂ propagationÂ inÂ fourthgrade elementary school students inÂ the firstÂ cycle Kajar mastery learning as many as 15 students or 62.5% andtheÂ averageÂ val ueÂ ofÂ 7.02Â classes.Â ResultsÂ onÂ theÂ secondÂ cycleÂ showedÂ anÂ increaseÂ inÂ theÂ graduat i onÂ rateÂ of 91.7% andÂ an average value ofÂ Â 7.45Â classes.Â On the implementation of the two cycle, mastery learning studentsandÂ theÂ averageÂ classÂ hasÂ reachedÂ theÂ indicator,Â so thatÂ theÂ secondÂ cycleÂ ofÂ Â this researchÂ isÂ successful ,Â inÂ otherwordsÂ theÂ studyÂ isÂ completedÂ inÂ theÂ secondÂ cycle.Â BasedÂ onÂ theÂ result sÂ ofÂ t heÂ studyÂ itÂ canÂ beÂ concludedÂ thatlearningÂ throughÂ gamesÂ bridgingÂ wallÂ propagationÂ canÂ improveÂ learningÂ outcomesÂ bridgingÂ inÂ gradeÂ IVElementaryÂ SchoolÂ Â DistrictÂ KajarÂ LasemÂ RembangÂ AcademicÂ YearÂ 2013.Â TheÂ resultsÂ ofÂ thisÂ studyÂ canÂ beapplied as oneÂ alternative learningÂ usedÂ toÂ improve student learningÂ outcomes.